Deep-Phenotyping the Less Severe Spectrum of PIGT Deficiency and Linking the Gene to Myoclonic Atonic Seizures - Bayat, Allan; Pendziwiat, Manuela; Obersztyn, Ewa; Goldenberg, Paula; Zacher, Pia; Döring, Jan Henje; Syrbe, Steffen; Begtrup, Amber; Borovikov, Artem; Sharkov, Artem; Karasińska, Aneta; Giżewska, Maria; et al. (Frontiers in Genetics, 2021)
The two aims of this study were i) to describe and expand the phenotypic spectrum of PIGT deficiency in affected individuals harboring the c.1582G>A; p.Val528Met or the c.1580A>G; p.Asn527Ser variant in either homozygous or compound heterozygous state, and ii) to identify potential genotype-phenotype correlations and any differences in disease severity among individuals with and without the PIGT variants. The existing literature was searched to identify individuals with and without the two variants. A detailed phenotypic assessment was performed of 25 individuals (both novel and previously published) with the two PIGT variants. We compared severity of disease between individuals with and without these PIGT variants. Twenty-four individuals carried the PIGT variant Val528Met in either homozygous or compound heterozygous state, and one individual displayed the Asn527Ser variant in a compound heterozygous state. Disease severity in the individual with the Asn527Ser variant was compatible with that in the individuals harboring the Val528Met variant. While individuals without the Asn527Ser or Val528Met variant had focal epilepsy, profound developmental delay, and risk of premature death, those with either of the two variants had moderate to severe developmental delay and later onset of epilepsy with both focal and generalized seizures. Individuals homozygous for the Val528Met variant generally became seizure-free on monotherapy with antiepileptic drugs, compared to other PIGT individuals who were pharmaco-resistant. Two patients were diagnosed with myoclonic-atonic seizures, and a single patient was diagnosed with eyelid myoclonia. Our comprehensive analysis of this large cohort of previously published and novel individuals with PIGT variants broadens the phenotypical spectrum and shows that both Asn527Ser and Val528Met are associated with a milder phenotype and less severe outcome. Our data show that PIGT is a new candidate gene for myoclonic atonic epilepsy. Our genotype-phenotype correlation will be useful for future genetic counseling. Natural history studies of this mild spectrum of PIGT-related disorder may shed light on hitherto unknown aspects of this rare disorder.